Logistics Distribution Retrieval Support System Using Analytical Hierarchy Process Method - Romualdus Vanadio Yoga S (Institute of Computer Science (IOCS), 2021)
Logistics Distribution Decision Making Support System is a computer-based information system that can be used to help distributors to distribute logistics in accordance with what is desired. The distributor in this context is the Regional Disaster Management Agency (BPBD) of Magelang Regency Logistics Division. In this system, the distributor will get a result in the form of a decision recommendation that is made based on the distribution's assessment for each prospective beneficiary area. The distribution assessment is determined by the number of criteria used, namely the amount of damage and loss (JKK), category of damage (KK), cost of proposed funds (BuD). In this system, the Analytical Hierarchy Process method is used to determine the comparison of assessments for each candidate area. This method was chosen because it has a hierarchical structure, which is in accordance with the core of the problem in selecting each regional candidate. The distribution of logistics with the Analytic Hierarchy Process method is able to get regional results that are the priority of logistics distribution with an error rate of 17.24% to 23.78%. The results obtained are the difference between the system and excel scores divided by the excel scores. The results obtained, can be used to help distributors carry out logistics distribution to potential natural disaster areas, and will only help (find the best solution) and not be the main benchmark in logistics distribution.